MODERN TRENDS IN THE METHODOLOGY OF TEACHING THE RUSSIAN LANGUAGE AND LITERATURE - Shakirova Iroda Utkurovna (Bright Mind Publishing, 2026)
This article provides a scientific-theoretical and practical analysis of modern trends in the methodology of teaching the Russian language and literature. It highlights the significance of a competency-based approach, learner-centered education, and the use of interactive and innovative methods in the teaching process. In addition, the article substantiates the importance of integrating information and communication technologies into education, ensuring interdisciplinary connections, and enhancing the educational and formative potential of literary instruction. The research findings are significant in that they contribute to improving the effectiveness of teaching the Russian language and literature and to developing students’ communicative, critical, and cultural competencies.
Keywords: Russian language and literature, teaching methodology, modern trends, competency-based approach, learner-centered education, innovative pedagogical technologies, information and communication technologies, interactive methods, interdisciplinary integration.